Acute intermittent porphyria exacerbation following in vitro fertilization treatment - Geok Huey New; Pei-Yang Hsu; Meng-Hsing Wu (Elsevier, 2016)
Objectives: Assisted reproductive technology is commonly used for women with infertility. We report a case of acute intermittent porphyria associated with in vitro fertilization treatment. Case Report: A 35-year-old woman with tubal factor infertility presented to our clinic with persistent low abdominal pain and hyponatremia after transvaginal oocyte retrieval. During admission, she experienced a generalized tonic-clonic seizure attacked following by dark brown color urine. Urinary tests showed elevated porphobilinogen, 5-aminolevulinic acid, uroporphyrin, and coproporphyrin, confirming the diagnosis of acute intermittent porphyria. The patient's condition continued to improve after hemin treatment and rehabilitation. Conclusion: Newly onset acute intermittent porphyria during the course of controlled ovarian hyperstimulation for in vitro fertilization is a rare but possible complication. Acute intermittent porphyria should be taken into consideration for persisted unexplained abdominal pain and seriously alerted if accompanied with neurological symptoms. Special tests for acute intermittent porphyria should be taken into consideration for the differential diagnosis of lower abdominal pain after oocyte retrieval.